Empowering or misleading? Online health information provision challenges. Issue 7 (3rd October 2016) - Dahl, Stephan; Eagle, Lynne
Abstract : Purpose: Patient empowerment (PE) is a key public health policy tool globally which is seen as unproblematic, but contains a number of unwarranted assumptions and unrecognised challenges to achieving effective implementation. Further, the theoretical foundations for understanding the impact of persuasive health communications on PE are weak. The purpose of this paper is to review these factors and to highlight major areas of concern. Design/methodology/approach: First, the assumptions underpinning empowerment and the implicit theoretical foundations for active health information seeking behaviours are reviewed. This is then followed by a readability analysis of internet-based material relating to two general medical conditions, four chronic medical conditions and six patient information leaflets which was conducted to explore issues relation to the provision and readability of online health information. Findings: The assumptions underpinning expectations of policy makers and health organisations regarding active health information seeking are shown to be problematic, with several potential impediments to effective PE implementation, including the fact that almost all of the online material reviewed is written in language too complex for the majority of the general public to comprehend, let alone act on. Practical implications: Recommendations are made for guiding information seeking and a research agenda is outlined that would aid in strengthening theoretical underpinnings, expand knowledge and thereby help inform practice and policy debate regarding how PE can be improved. Originality/value: This paper contributes to understanding of the challenges of effective health communication in the digital age by highlighting the need for a greater understanding of online health information seeking and the impact of limited health literacy and numeracy.